Analisis Pengaruh Kebijakan Moneter terhadap Perdagangan Internasional Indonesia - Adelia Safitri; Dini Anggraini; Mutia Salwa Hutahuruk; Maryam Batubara (Economic Reviews Journal, 2024)
This study aims to analyze the impact of monetary policy on Indonesia's international trade using a literature review approach. The monetary policy implemented by Bank Indonesia, particularly concerning interest rates, inflation, and the exchange rate of the rupiah, significantly affects the performance of international trade. This study collects, evaluates, and synthesizes information from various relevant literature sources, including scholarly journal articles, books, research reports, and policy documents. The findings indicate that interest rates influence the competitiveness of export products through production costs, controlled inflation boosts foreign direct investment flows, and exchange rate stability supports long-term business planning and investment. Effective monetary policy can help create a stable trade environment, enhance the competitiveness of Indonesian products in the global market, and strengthen the country's economic position in the global supply chain.